Macroeconomic Performance and Poverty Reduction - Epaulard, Anne. (Washington, D.C. : International Monetary Fund, 2003)
This paper investigates the link between macroeconomic performance and the change in the poverty rate among 47 episodes of growth and 52 episodes of economic downturn in developing and transition economies. We show that, on average, (i) the greater the inequality, the lower the elasticity of poverty to growth, and the higher the mean income, the higher the elasticity; (ii) the country-specific elasticity is identical for episodes of economic growth and for episodes of economic downturn; and (iii) higher growth does not bring diminishing returns to poverty reduction. Moreover, we show that very high inflation is associated with a higher elasticity of the poverty rate to economic downturn, but at lower inflation, there is no relationship between inflation and the elasticity of the poverty rate to growth or recession. Trade openness and changes in the terms of trade explain part of the elasticity of the poverty rate to economic downturn.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet